EVALUASI PERTUMBUHAN DAN DAYA HASIL 9 CABAI HIBRIDA - Arya Widura Ritonga; Muhamad syukur; Sriani Sujiprihati; Dimas Purwo Anggoro (Jurnal Floratek, 2016)
Planting pepper hybrid varieties offers an alternative strategy to meet needs of chili pepper in Indonesia. The aim of the experiment waere to evaluate and select nine pepper hybrids thus obtained peppers hybrid potential to be released as hybrid varieties of chili pepper. The experimental design used was Randomized Complete Block Design (RCBD) with one factor and three replications. Plant mateterials were nine pepper hybrid and five commercial hybrid of chili peppers. IPB CH3, IPB CH50 and IPB CH28 pepper hybrid  produced higher selection index value than comercial hybrid of chili pepper. The IPB IPB CH3, IPB CH50 and IPB CH28 pepper hybrid were potential to be released as hybrid varieties of chili pepper.